Predictors of vulnerability type among poor fisheries community members using gender analysis in Northern States in Malaysia - Saidi, Norehan (2021)
This study aims to profile the backgrounds of the vulnerable respondents, to identify the distributions of the vulnerable respondents by the vulnerability type, to measure the relationship between two levels of household income and two types of water system community, and to predict the best vulnerability type to explain the likelihood of the vulnerable respondents in the poor category household income by two types of water system community involve in fisheries and aquaculture economic sector (FAES). All the research objectives were sex disaggregated. In this study two data sets were used, which were Data 01 (brackish water community) and Data 02 (freshwater community), which covered the backgrounds of the vulnerable respondents and the household income used in this study from the respective questionnaires. In both data sets, the respondents were vulnerable, which were sampled through multiple level random sampling with assistance from government agencies and the community leaders in the sampled villages at Padang Terap, Kedah; Hulu Perak, Perak; Pulau Langkawi, Kedah; and Kota Setar, Kedah; all in Northern Peninsular Malaysia. The vulnerable respondents suffer at least one vulnerability type as deduced from the Sustainable Livelihood Approach. A total of 415 vulnerable respondents reported in this study who were mainly females in brackish water (58.84%) and males (58.14%) in freshwater communities. According to the mean age, the respondents in this study were older people (mean age> 60 years old), with low academic background, mostly married males (79.07 %), single females (64.61%), and many males had house ownership (81.40%). The male vulnerable respondents mainly suffered from the Handicapped Vulnerability Type and the female suffered the Single Parent Vulnerability Type. Among the females the mean household income=RM960.74 and they were poorer than the male vulnerable respondents with a mean household income=RM1481.28. There was a significant (p<0.05) relationship between two levels of household income (PLI=RM980 as a cut-off point) and two types of water system community among the male and female vulnerable respondents. Thus, HO1 and HO2 were rejected. Male and female vulnerable respondents were poorer in brackish water than in freshwater communities. One Binary Logistic Regression Model for the four null hypotheses was tested in order to identify the vulnerability type to predict the vulnerable respondents in the poor category of household income in two types of water system community. All model fits were significant (p<0.05), thus all four null hypotheses were rejected. The Single Parent Vulnerability Type significantly (p<0.05) and negatively predicted single father and positively predicted single mothers in the poor category of household income in the brackish water and freshwater communities. In addition to the Single Parent Vulnerability Type among females in the freshwater community, the Living Alone Vulnerability Type also significantly predicted (p<0.05) them as being in the poor category of household income. In conclusion, poverty is related to single mothers and females living alone, and, in the brackish water community, it is mainly related to old women. A relationship between gender, poverty, and vulnerability in masculine FAES is found in this study. Single mothers and the old women staying alone should be given high attention in terms of policies and programmes in fisheries communities, especially to achieve SDG1, SDG2, SDG 5, and SDG10.